Tigray Orthohantavirus Infects Two Related Rodent Species Adapted to Different Elevations in Ethiopia - Meheretu, Yonas; Stanley, William T; Craig, Evan W; Goüy de Bellocq, Joëlle; Bryja, Josef; Leirs, Herwig; Pahlmann, Meike; Günther, Stephan (Vector borne and zoonotic diseases (Larchmont, N.Y.), 2019)
Orthohantaviruses are RNA viruses that some members are known to cause severe zoonotic diseases in humans. Orthohantaviruses are hosted by rodents, soricomorphs (shrews and moles), and bats. Only two orthohantaviruses associated with murid rodents are known in Africa, Sangassou orthohantavirus (SANGV) in two species of African wood mice (Hylomyscus), and Tigray orthohantavirus (TIGV) in the Ethiopian white-footed rat (Stenocephalemys albipes). In this article, we report evidence that, like SANGV, two strains of TIGV occur in two genetically related rodent species, S. albipes and S. sp. A, occupying different elevational zones in the same mountain. Investigating the other members of the genus Stenocephalemys for TIGV could reveal the real diversity of TIGV in the genus.
Keywords: Stenocephalemys; Hantavirus; hantavirové infekce; Rodent Diseases; Simien Mountains; nemoci hlodavců; Afroalpine; Rodentia; zvířata; Humans; hlodavci; Etiopie; fylogeneze; orthohantavirus; Species Specificity; Ethiopia; Hantavirus Infections; Orthohantavirus; druhová specificita; phylogeny; Phylogeny; lidé; Animals